Quality control manual for KIMCHI (fermented chinese cabbage, Brassica Pekinensis) production - Benedicto, Ronald P.; Dumelo,d Benelyn Domingo (1993.)
The purpose of this activity was to create a quality control manual for kimchi production. A preliminary study was conducted in order to verify the process used for preparation of kimchi at laboratory scale. Two critical factors affecting kimchi formulation were identified: spiciness and saltiness. Phase I involved the development of a standard formulation using a two-level, two-factor experimental design, the two factors being red chili powder and salt. The high and low levels for red chili powder were 0.47% and 0.23% respectively, while for salt 1.5% and 0.6%. The most acceptable formulation was F4 with 0.47% red chili powder and a 1.5% salt. A product profile was created for the standardized formulation. Phase II involved first, the translation of the process and formulation to bench scale. During bench scale production, specifications for raw materials, process control and finished products were developed using objective as well as subjective tests. Statistical analysis showed that the process and formulation were repeatable within scales and across scales (save for color evaluation). Phase II involved the development of a quality control manual. It contained the results of the objective tests as well as the procedures for carrying out these tests (as part of the Exhibits.)
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Vegetables -- Preservation -- Quality control; Vegetables -- Preservation -- Handbooks, manuals, etc